(3ZQQ CfHGA fLHGA GdGHfGAs - (3CHh YHO Gddg eMeO Hf eMeO Hf CHi GdbGSe Hf Ydj GdbQTi GdeYQha HGHf XaQ,J (B565 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeMehO HGbhGd GdegJOjf HGf LYd ef PQjGQGJge ef gh bQI Yjf hZQI Rjf abGd Rjf GdfGS MH GdTghGJ ef GdfSGA hGdfHjjf hGdbfGWjQ GdebfWQI ef GdPgH hGdaVI s
(3BNQgG (B:s
(3gPG GdPi McjJg Yf HgQGe ChQOg eMeO GHf MQjQ hdf jfcQ Pdc ef hba Ydi NUjU s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B230 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdCOHs